Preparing for a warmer world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Agriculture, fisheries and forestry have traditionally provided the main sources of food and income for ACP islands. But these livelihoods are increasingly threatened by climate change, mostly caused by emissions on the other side of the globe.